2016
DOI: 10.3168/jds.2015-10132
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in adipose tissue of dairy cows from late pregnancy to lactation. Part 2: The SIRT-PPARGC1A axis and its relationship with the adiponectin system

Abstract: The transition period in dairy cows is characterized by major changes in glucose and adipose tissue metabolism. The Sirtuin-1 (SIRT1) PPARγ co-activator 1α (PPARGC1A) axis might be related to the adiponectin (ADIPOQ) system to orchestrate the regulation of these processes. We aimed to assess the mRNA abundance of the aforementioned components in one visceral and one subcutaneous fat depot, together with the ADIPOQ concentrations in serum of dairy cows from late gestation to early lactation. In addition, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…This was further supported by the fact that in the present study differences disappeared after 21 DIM when cell size is not different between depots anymore (Kenéz et al, 2015). Furthermore, the mentioned companion studies of Weber et al (2016aWeber et al ( , 2016b again confirm higher lipolytic potential in RPAT compared to SCAT due to differences in mRNA and protein expression of several effectors of lipolytic pathways. In the present study, MAT showed the biggest adL during fresh cow period.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This was further supported by the fact that in the present study differences disappeared after 21 DIM when cell size is not different between depots anymore (Kenéz et al, 2015). Furthermore, the mentioned companion studies of Weber et al (2016aWeber et al ( , 2016b again confirm higher lipolytic potential in RPAT compared to SCAT due to differences in mRNA and protein expression of several effectors of lipolytic pathways. In the present study, MAT showed the biggest adL during fresh cow period.…”
supporting
confidence: 85%
“…Furthermore, the mentioned companion studies of Weber et al . (2016 a , 2016 b ) again confirm higher lipolytic potential in RPAT compared to SCAT due to differences in mRNA and protein expression of several effectors of lipolytic pathways. In the present study, MAT showed the biggest adL during fresh cow period.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, SIRT3 deacetylates FOXO3 to protect mitochondria against oxidative stress (Tseng et al 2013). The existence of the SIRT1-peroxisome proliferator-activated receptor (PPAR) GC1A-axis has been demonstrated in dairy cows and indicates a functional relationship between SIRT1 and adiponectin type 1 receptor in bovine adipose tissue (Weber et al 2016).…”
Section: Mitochondrial B-oxidationmentioning
confidence: 99%
“…Tissue homogenates (500 mg/mL) for WB were prepared with 10 mM HEPES, pH 7.4, according to Weber et al (2016). Samples were diluted to 0.5 mg of total protein/mL with water and mixed with loading buffer (final concentrations: 0.1 M Tris HCl pH 6.8, 1% SDS, 0.0032% bromophenol blue, 10% glycerol).…”
mentioning
confidence: 99%